Gamma-ray dosimetric properties of conjugated polymers in solution - Batagin Neto, Augusto [UNESP]; Bronze-Uhle, Erika Soares [UNESP]; Vismara, Marcus Vinícius Gonçalves [UNESP]; Assis, Andrei Paulo de [UNESP]; Castro, Fernando Araújo de [UNESP]; Lavarda, Francisco Carlos [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Bentham Science Publishers, 2013)
The effect of gamma radiation on poly{[2,5-bis(3-(N,N-diethylamino)-1-oxapropyl)-1,4-phenylene]-alt-1,4- phenylene} (PPP); poly{[2,5-bis(3-(N,N-diethylammonium bromide)-1-oxapropyl)-1,4-phenylene]-alt-1,4-phenylene} (PPP-Br); and the polymerized dye poly-1-ethyl-2-[3-(1-ethyl-1,3-dihydro-3,3-dimethyl-2H-indol-2-ylidene)-1-propenyl]- 3,3-dimethyl-3H-indolium perchlorate (Poly-CyC) has been investigated. The stability and response of poly [2-methoxy- 5-(2'- ethyl-hexyloxy)-p-phenylenevinylene] (MEH-PPV) in mixed solutions have also been explored. To this end, samples with concentrations ranging from 0.005 to 0.500 mg/mL were irradiated with a 60Co gamma-ray source at room temperature, using doses up to 1 kGy, and the response was analyzed by UV-Vis spectroscopy. The obtained results reinforce the previously proposed mechanism and suggest that the effect depends on specific structural characteristics of the main chain of the polymers. Moreover, the polymerized dyes display interesting dosimetric properties. Additionally, it has been noted that, contrary to what happens in other solvents, MEH-PPV is degraded in bromoform solution. Protective effects have also been observed for bromoform+toluene mixtures (1:1 vol/vol) and solutions containing molecular dyes. - See more at: http://www.eurekaselect.com/117251/article#sthash.gHFnYvJk.dpuf
Keywords: Dosimetry; Dyes; Electronic structure; Fukui indices; Gamma-ray effects; Halogenated solvents; Infrared spectra; MEH-PPV; Polymer solutions; Polymer structure; Poly-CyC; PPP; Radiolysis; Stability